2020
DOI: 10.1093/mnras/staa1676
|View full text |Cite
|
Sign up to set email alerts
|

Empirical completeness assessment of the Gaia DR2, Pan-STARRS 1, and ASAS-SN-II RR Lyrae catalogues

Abstract: ABSTRACT RR Lyrae stars are an important and widely used tracer of the most ancient populations of our Galaxy, mainly due to their standard candle nature. The current availability of large-scale surveys of variable stars is allowing us to trace the structure of our entire Galaxy, even in previously inaccessible areas like the Galactic disc. In this work, we aim to provide an empirical assessment of the completeness of the three largest RR Lyrae catalogues availab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, our result is unaffected as long as the completeness is constant within the survey volume. Indeed, according to Figure 13 of Mateu et al (2020), the completeness of the RR Lyrae sample in Gaia DR2 at |𝑏| > 20 • is almost insensitive to the 𝐺-magnitude at 14 < 𝐺 < 18, where most of our sample reside. Thus, the simple selection function model in the above equations is reasonable for our analysis.…”
Section: Selection Function Modelmentioning
confidence: 84%
“…However, our result is unaffected as long as the completeness is constant within the survey volume. Indeed, according to Figure 13 of Mateu et al (2020), the completeness of the RR Lyrae sample in Gaia DR2 at |𝑏| > 20 • is almost insensitive to the 𝐺-magnitude at 14 < 𝐺 < 18, where most of our sample reside. Thus, the simple selection function model in the above equations is reasonable for our analysis.…”
Section: Selection Function Modelmentioning
confidence: 84%
“…Of these, only 12 (six) are also consistent with the kinematic signature we detected in the space of l-b-pmra-pmdec 6 . Based on these results, and after correcting for the completeness of the RR Lyrae catalogue (estimated at 80% at these magnitudes in Mateu et al 2020), we conclude that MNC has, at most, 15 RR Lyrae and that the ACS has no more than eight. In parallel, we crossmatched the list of RR Lyrae with our sample to see the effect that the cut in parallax 12 has, and we observed that, from the 253 (253) stars that we had, only 123 (123) remain in MNC (ACS).…”
Section: Rr Lyrae To M Giant Ratiomentioning
confidence: 82%
“…Starting with the RR Lyrae, we used the catalogue described in Mateu et al (2020), which combines the VariClassifier and Specific Objects Studies (SOS) catalogues from Gaia DR2 (Holl et al 2018;Clementini et al 2019) with the ASAS-SN-II catalogue Jayasinghe et al (2019), providing optimal completeness at the bright end (G < 15). We selected only those sources that fall within the sky patches defined in Fig.…”
Section: Rr Lyrae To M Giant Ratiomentioning
confidence: 99%
“…Gaia Data Release 2 provided such a sample 52,53 . However, these maps are incomplete at the depths necessary to detect RR Lyrae at > 60 kpc (G ≈ 20), driven largely by the Gaia scanning pattern 54 . For example, the local wake is not clearly visible in the Gaia RR Lyrae catalog despite the fact that it is so prominent in the Pan-STARRS data at > 60 kpc.…”
Section: The Stellar Halo Probed By Rr Lyraementioning
confidence: 99%